PROSES EVALUASI KOLEKSI YANG DILAKUKAN DI PERPUSTAKAAN SMA MUHAMMADIYAH 4 YOGYAKARTA - Irzalina Rahmawati (Jurnal Pustaka Ilmiah, 2019)
ABSTRACTThe purpose of this study was to determine the collection evaluation process carried out in the Senior High School of Muhammadiyah 4 Yogyakarta library with the benefits of research, that is as a matter of consideration in conducting evaluations in the development of collections carried out at the library so that the collections are in accordance with user needs. The research method used is the method of observation, interviews, and documentation. Based on observations, interviews, and documentation with librarian at Senior High School of Muhammadiyah 4 Yogyakarta, we can conclude the following results: Library evaluation in the Senior High School of Muhammadiyah 4 Yogyakarta includes 4 processes that is collecting all collections of data, check the list of standards such as catalogs and bibliographies, gathering opinions from users who normally come to the library, and direct collection checks.